Codon optimization, expression and purification of recombinant Pwo DNA polymerase in E. coli - Nguyen, Van Sang; Huyen Nguyen, Thi Thu (Vietnam Journal of Biotechnology, 2023)
Pwo DNA polymerase is an enzyme that is widely used in PCR due to its thermal stability and proofreading activity (3′-5′ exonuclease activity) with high accuracy. Optimizing the expression and purification of the protein is crucial to reducing the cost of production for this important enzyme. In this study, the higher expression level of the gene encoding Pwo DNA polymerase in bacteria strain E. coli BL21(DE3) was achieved by optimizing codon usage. The parameters of the gene encoding Pwo DNA polymerase obtained from the optimization: Number of Codons (ENc) = 28; Codon Adaptation Index (CAI) = 0.94; %GC = 48.4%. The codon-optimized gene was cloned into a pET-M expression vector and successfully expressed the Pwo DNA polymerase protein with a 6xHis-tag in E. coli BL21(DE3) cells. The recombinant protein was purified through a simple and rapid process involving two steps: cell lysis at high temperature combined with affinity chromatography using a Nickel column. The amount of Pwo DNA polymerase enzyme obtained from 1 liter of cell culture reached 32 mg. The protein yield in this study is higher than that of previous research while maintaining activity comparable to commercial enzymes. The activity of the Pwo DNA polymerase enzyme was tested at concentrations ranging from 60-150 µg/ml which showed to be equivalent or better than the commercially available Taq DNA polymerase from Promega. This result actively contributes to the production of the Pwo DNA polymerase enzyme and the study of its variants in the future.